Chronic osteomyelitis of the jaws: A 7-year retrospective clinico-surgical evaluation in a tertiary hospital in Northwest Nigeria - Mujtaba Bala; Ramat Oyebunmi Braimah; Abdulrazaq Olanrewaju Taiwo; Sufiyanu Umar Yabo; Bashar Aliyu (Wolters Kluwer Medknow Publications, 2023)
Background: The incidence of chronic osteomyelitis of the jaw has declined in the developed world. However, it is still a burden in Northwestern Nigeria. Chronic osteomyelitis of the jaw occurs more commonly in the mandible, with sequestrectomy or jaw resection being the main treatment modality for the developing climes. Objective: The objective of this study was to describe the pattern of clinical presentation of this disease condition and to highlight the important aspects of its management. Methods: This was a retrospective analysis of chronic osteomyelitis seen and managed over a 7-year period. Sociodemographics, etiology, clinical features, investigations, and treatment modality were analyzed using SPSS version 25.0. Results: There were 36 (73.5%) males and 13 (26.5%) females in the age range of 7-87 years, with a mean ± standard deviation of 27.67 ± 21.13 years. The duration of symptoms ranged from 4 months to 3 years. Odontogenic infections were the main cause of osteomyelitis (44 [89.8%]), and the mandible (39 [79.6%]) was the most affected maxillofacial bone. The presenting complaints included pain, discharging sinuses, and swelling. Comorbidities, such as diabetes and hypertension, were recorded in five patients (10.2%). Plain radiographs and computed tomography scan were the imaging modalities. The majority, 36 (73.5%), had a sequestrectomy. There was no statistically significant difference between the affected jaw and the type of surgical procedure performed (χ2 = 1.801, df = 2, P value 0.406). Conclusion: This study found chronic osteomyelitis to be more common in the mandible and was mainly caused by an odontogenic infection. Prolonged antibiotic use, sequestrectomy, and jaw resection were used as the main approaches to its management in our locality.